Multiplex Real-Time PCR Assay for the Detection and Differentiation of Poxviruses and Poxvirus Vectors. (December 2015) - Stellberger, Thorsten; Stockmar, Iris; Haase, Maren; Meyer, Hermann; Zoeller, Gudrun; Pavlovic, Melanie; Büttner, Mathias; Konrad, Regina; Lang, Heike; Tischer, Karsten; Kaufer, Benedikt B.; Busch, Ulrich; et al.
The Chordopoxvirinae subfamily ( Family Poxviridae) includes human and animal pathogens with zoonotic potential. Among them are viruses that are commonly used as viral and vaccination vectors, some of them bearing oncolytic or oncotropic potential for anti-tumor therapy. The authors have developed a versatile triplex real-time PCR assay that facilitates differentiation between the genera (i) Orthopoxvirus, (ii) Avipoxvirus, and (iii) Parapoxvirus and Molluscipoxvirus. Hydrolysis probes labelled with Yakima Yellow, Cy5, and FAM specifically bind to Ortho-, Avi-, Para- or Molluscipoxviruses, respectively. The authors detected the expected four poxvirus genera in purified DNA from 47 poxviral samples, whereas four samples belonging to the genera Yatapoxvirus and Capripoxvirus were not detected. Taken together, a set of 24 negative controls comprising other viruses including non-target poxvirus-genera as well as bacteria, yeast, mammal, and avian cells were tested to proof the specificity of the assay. Probit analysis revealed a detection limit of three copies per reaction (95% confidence level) for the Ortho-, Avi-, and Para-/Molluscipoxvirus-PCR using two independent Cycler-Master mix combinations.